Electrochemical oxidation of paracetamol mediated by zinc oxide modified glassy carbon electrode - Mohammed Zidan; Tan, Wee Tee; Abdullah, Abdul Halim; Zainal, Zulkarnain; Goh, Joo Kheng (American-Eurasian Network for Scientific Information, 2010)
Zinc oxide (ZnO) microparticles have been mechanically attached on the surface of a glassy carbon (GC) electrode. The purpose of this paper is to critically examine the modification of GC electrode with Zinc oxide microparticles and the effect on oxidation of paracetamol in 0.1 M KH2PO4 electrolyte solution by cyclic voltammetry (CV). Excellent electrocatalytic activity towards the oxidation of paracetamol was observed. Peak potential was observed to current was significantly enhanced by about 1.1 folds as compared to bare GC electrode shift slightly to less positive value by about 150 mV and. The sensitivity under conditions of cyclic voltammetry is significantly dependent on pH and scan rate. The variation of scan rate study shows that the system undergoes diffusioncontrolled process. In addition, calibration plot reveals linearity from the range 2.0 × 10-5 to 5.0 × 10-3M with a correlation coefficient of 0.997.